2009
DOI: 10.1517/14728220902882130
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective and clinical potential of statins in dialyzed patients

Abstract: Background: The combination of increased cardiovascular mortality and vascular complications due to dyslipidaemia in chronic kidney disease (CKD) has focused attention onto the potential beneficial effects of 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMG-CoA) inhibitors (statins) on the course of CKD. Objective: To examine the use of statins in CKD. Methods: A review of relevant literature. Results/conclusion: Current evidence from clinical trials in CKD patients on maintenance dialysis is limited. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 78 publications
(51 reference statements)
1
17
0
Order By: Relevance
“…Moreover, the presence of dyslipidemia in these patients might enhance the rate of decline in renal function and chronic kidney disease (CKD) progression, generally by raising the inflammation and the oxidative stress in the renal microenvironment [143][144][145][146]. In the post-hoc analyses of randomized controlled trials (RCTs) the benefits of statins in myocardial infarction (MI) also extend to patients with mild-to-moderate renal insufficiency [147], but these patients are more prone to CVD than progress to end-stage kidney disease [147].…”
Section: Kidney Diseases and Statin Intolerancementioning
confidence: 99%
“…Moreover, the presence of dyslipidemia in these patients might enhance the rate of decline in renal function and chronic kidney disease (CKD) progression, generally by raising the inflammation and the oxidative stress in the renal microenvironment [143][144][145][146]. In the post-hoc analyses of randomized controlled trials (RCTs) the benefits of statins in myocardial infarction (MI) also extend to patients with mild-to-moderate renal insufficiency [147], but these patients are more prone to CVD than progress to end-stage kidney disease [147].…”
Section: Kidney Diseases and Statin Intolerancementioning
confidence: 99%
“…The most common changes being lowered high density lipoprotein cholesterol (HDL-C) levels and elevated level of triglycerides (TG) 3 ; hypercholesterolemia per se might be present in around 50% of patients on dialysis 7 . Among lipid lowering drugs, statins are the most effective in improving the lipid profile and cardiovascular (CV) outcomes in patients with CKD [5][6][7][8][9][10] . However, despite several studies and meta-analyses there are still questions regarding their role in CKD.…”
Section: I a L D I S T R I B U T I O N U N A U T H O R I Z E D U S mentioning
confidence: 99%
“…They also do not give detailed recommendations on combined therapy in lipid disorder patients, which seems to be a future method of dyslipidaemia treatment, for example in patients with chronic kidney disease (CKD). The recent Study of Heart and Renal Protection (SHARP) trial with simvastatin and ezetimibe showed 17% reduction in major atherosclerotic events and 15.3% in major vascular events in CKD [4,11,12].…”
Section: Lipidology Update 2011mentioning
confidence: 99%